2007
DOI: 10.1001/jama.298.19.2289
|View full text |Cite
|
Sign up to set email alerts
|

Association of Posttherapy Positron Emission Tomography With Tumor Response and Survival in Cervical Carcinoma

Abstract: ContextRetrospective studies have demonstrated that the use of positron emission tomography (PET) with F-18 fluorodeoxyglucose (FDG) in the posttherapy evaluation of patients with cervical carcinoma is predictive of survival outcome.Objective To validate the association between the metabolic response on the 3-month posttherapy FDG-PET and long-term survival outcome. Design, Setting, and PatientsA prospective cohort study designed to validate our previous finding that the results of a 3-month posttherapy FDG-PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
162
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 272 publications
(169 citation statements)
references
References 44 publications
5
162
0
2
Order By: Relevance
“…For initial staging,85% of respondents considered pet to be a standard of care, and nearly half (45%) believed it should be a standard of care to assess treatment response. Because of access survival 3 . Other authors have evaluated pet as an aid to brachytherapy planning 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For initial staging,85% of respondents considered pet to be a standard of care, and nearly half (45%) believed it should be a standard of care to assess treatment response. Because of access survival 3 . Other authors have evaluated pet as an aid to brachytherapy planning 4 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to initial stage and lymph node status, posttreatment response based on pet-ct strongly predicts for disease recurrence 3 . Schwarz et al prospectively evaluated pet-ct imaging 3 months after therapy in advanced cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Posttreatment disease response was assessed by a nuclear medicine physician reading a diagnostic FDG‐PET/CT scan performed on average 3.1 months after the conclusion of the CCRT, as previous studies have shown that the 3‐month posttreatment time point correlates with long‐term outcome 17. Treatment outcome measures were complete metabolic response (CMR), PD, or new disease (ND).…”
Section: Methodsmentioning
confidence: 99%
“…According to Grigsby et al [9], PET is valuable to evaluate the response to treatment and for the surveillance of patients after initial therapy. Schwartz et al [10], in their prospective study on 92 patients after chemoradiation, showed that the 3-year progression-free survival rates, according to the metabolic response, were 78 % for a complete response, 33 % for partial response, and 0 % for progressive disease. The major advantage of 18F-FDG-PET in cervical cancer is the diagnosis of relapse.…”
Section: Cervical Cancermentioning
confidence: 99%